Changes of lymphocrte function in obstructive jaundiced states - KATO, Fumihiko; AKAMO, Yoshimi; MURAMOTO, Masayuki; TAKAOKA, Tetsuro; FUKUI, Takuji; SHIBATA, Kiyohito (Tando, 1992)
A clinical and exprimental evaluation on lymphocyte transformation ability under jaundiced state, and the effect of serum obtained from jaundiced subjects were performed, giving the following results. 1) the lymphocyte's transformation ability was proven to be decreased at jaundiced states both clinically and experimentally. 2) The serum obtained from jaundiced subjects, proved to contain an inhibitory substance against lymphocyte transformation. These results indicate that the reduction of the level of hyperbilirubinemia, is of value in terms of improving the patients'immunological strength, especially the lymphocyte's power.